Cyberbullying during the pandemic: an exploratory study about Romanian university students - Constantinescu, Sorana-Alexandra; Ghiman, Lorin; Pop-Cimpean, Adela (Przegląd Krytyczny, 2022)
With the switch to online teaching starting March 2020 due to the Covid-19 pandemic, students have spent more time than ever online. The study (N=191) was conducted online and answered the following research questions: 1) Does the time spent online influence students experience with cyberbullying? 2) Are students from vulnerable groups more prone to cyberbullying? 3) What are the ways students believe cyberbullying should be addressed? 4) Are there gender differences in the way cyberbullying is perceived? Among others, the study revealed that women are more likely to acknowledge cyberbullying and that their professors are identified by a large part of the sample as perpetrators of cyberbullying.